2010
DOI: 10.1111/j.1432-2277.2010.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of pancreas transplantation in patients older than 50 years

Abstract: Summary Aging of the population and improvements in diabetes therapy have led to an increased number of older pancreas transplant candidates. The aim of our retrospective study was to evaluate pancreas transplantation (PT) outcomes in patients ≥50 years, as limited data exist in these patients. We analyzed 398 consecutive pancreas transplant patients from June 1994 to June 2009 for different outcomes (patient/graft survival, rejection rate, and surgical complications) between the age groups ≥50 years (n = 69) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 36 publications
4
68
0
3
Order By: Relevance
“…Similar data exist among DDRT recipients, where the oldest recipients have the worst overall survival, but death-censored graft survival improves linearly with recipient age, suggesting either a beneficial immunosuppressive function of age or more aggressive disease in younger patients [46]. Regardless of mechanism, several other small retrospective institutional studies support the conclusion that recipient age is not a primary risk factor for patient mortality or graft failure and that PT in appropriately selected recipients >50 years of age still holds benefits [47,48].…”
Section: Older Recipientssupporting
confidence: 54%
“…Similar data exist among DDRT recipients, where the oldest recipients have the worst overall survival, but death-censored graft survival improves linearly with recipient age, suggesting either a beneficial immunosuppressive function of age or more aggressive disease in younger patients [46]. Regardless of mechanism, several other small retrospective institutional studies support the conclusion that recipient age is not a primary risk factor for patient mortality or graft failure and that PT in appropriately selected recipients >50 years of age still holds benefits [47,48].…”
Section: Older Recipientssupporting
confidence: 54%
“…Improvements in the physician's armamentarium to reduce the development of diabetic complications have lead to the emergence of a healthier aging population of type 1 diabetics in need of pancreas transplantation [1, 2]. Progress in surgical techniques, critical care, and immunosuppressive medications have also expanded the pool of transplant candidates to include a significant proportion of patients over the age of 50 [3].…”
Section: Introductionmentioning
confidence: 99%
“…This procedure may be considered as a group of three separate clinical entities: simultaneous pancreas and kidney transplantation (SPK), pancreas after kidney (PAK), and pancreas transplant alone (PTA) [1][2][3]. It has been shown that SPK, by inducing insulin independence and replacing native renal function, has beneficial effects on diabetes complications and prolongs life expectancy [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%